Tropeirismo e educação no caminho de palmas a Palmeira/Pr: limites e possibilidades de escolarização (1854-1916) - Muller, Bruna Aldine (2021)
The present research is linked to the line of research Society, Knowledge, and Education, of the Postgraduate Program in Education, Master's level, of the State University of Western Paraná - Francisco Beltrão campus and its research theme is the relationship between Tropeiro Movement and schooling in the area of influence of the Estrada de Palmas-Palmeira in the State of Paraná. The Estrada de Palmas-Palmeira was a branch of the Caminho das Missões, which sought to meet the commercial needs arising from the great Tropeirismo of the 19th century, allowing the transit of cattle from the missionary region and the Campos de Palmas to the Caminho de Viamão, which passed through the city of Palmeira. Given the historical, social, and cultural transformations that developed around this route belonging to the São Paulo Province until 1853, and later to Paraná, the present research aims to understand the relationship between Tropeirismo and the institutionalization of education in the area of influence of the Estrada Palmas-Palmeira, from 1854 to 1916. The temporal delimitation began in 1854, as it was the government's initial landmark in the Province of Paraná when the Paraná government started to organize public education and other sectors. The 1916 clipping marked the boundary agreement between the State of Paraná and Santa Catarina, a historic fact that characterized the end of the Contestado War and the configuration of new frontiers between the two states. The investigation is based on documentary sources, focusing on the analysis of the educational legislation of the period, reports from provincial presidents, reports from state governors, reports from public education inspectors and teachers, as well as bibliographic and iconographic sources. The adopted methodology is the documentary analysis, considering the context of the production of the sources and the crossing of the information/data revealed by the documentation. Given the above, we affirmed that the introduction of Tropeirismo in the region was important for exploring the territory and the dynamization of the establishment of the first colonizers. These tropeiros expelled and decimated the indigenous people and organized them into large estates, expanded the breeding and wintering of cattle, based on slave labor, in a religious and patriarchal society. In this structure, schooling linked to provincial policies was materialized with the implementation of isolated elementary schools. Faced with the insertion of new economic activities, there was a demographic increase and schooling gradually expanded. We concluded in this way, that the implementation of school institutions in Estrada de Palmas was incipient when the agropastoral activity integrated the structural aspects of this society because public schooling in this context was not an element of interest. To this end, the number of schools showed a relative increase when new economic activities rose and republican ideals began to be disseminated.